Importation grecque et activité métallurgique sur un habitat rural de la périphérie de Bourges - Laurent Fournier; Florent Mercey (Revue Archéologique du Centre de la France)
An archaeological diagnostic’s operation realised in Soye-en-Septaine, ten kilometers south-east from Bourges, allowed to discover a semi buried structure of a settlement dated to the 5th century BC. The filling of this pit delivered a lot of ceramic’s remains, among them a fragment of a red-figure attic cantharis. Fragments of pisolithic iron ore, broken in the heat, were found in the filling of this pit, and in the filling of another rear pit, attesting exploitation of these iron ores of Champagne berrichonne during this period.